Efektivitas Model Collaborative dengan Media Plotagon Story dalam Pembelajaran Bahasa Arab - Khairani Khairani; Wasilah Wasilah; Qoim Nurani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effectiveness of the collaborative learning model using Plotagon Story animated media in Arabic language learning, particularly in improving students’ speaking skills (maharah kalam). The research employed a (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants were 25 students at the MTs (Islamic Junior Secondary Level), selected through purposive sampling. The developed product was a collaborative based animated video adapted from the muhadatsah section of the textbook Arabiyah Linnasyi’in. The validation results indicate that the product is highly feasible, with a material expert score of 94% and a media expert score of 90%. The implementation stage involved applying the animated video in the learning process, followed by pre-test and post-test assessments. The paired sample t-test revealed a Sig. (2-tailed) value of 0.000 (<0.05), indicating a significant difference between students’ scores before and after using the media. The N-Gain score of 0.72 falls within the high category, with an effectiveness percentage of 72.68%. Therefore, the collaborative learning–based animated video developed using Plotagon Story is effective in enhancing the speaking skills of MTs level students and is suitable for use as a learning medium in Arabic language education. Keywords: collaborative learning, Plotagon Story, Arabic learning